Inter-ethnic relations among black students at a South African higher education institution - Mulondo, M.A.; Thomas, A.T. (South African Journal of Higher Education, 2021)
This study explored the inter-ethnic relations and experiences of students at a higher education institution, using an exploratory case study approach. Purposive sampling was used to select students belonging to black South African ethnic groups. Semi-structured interviews were used to collect data from three participants; interpretative phenomenological analysis was used for analysis. The themes extracted were ethnic identity: identity confusion vs. certainty; personal experiences of inter-ethnic relations; and majority and minority ethnic groups’ experiences. Identity salience was found to not particularly be integral to the cultivation of inter-ethnic relations. Moreover, participants’ inter-ethnic experiences were varied; some were positive, and others, negative. Relations between majority and minority ethnic groups are seemingly supported by existing literature, as majority ethnic group members typically initiated negative interactions, more so than did minority ethnic groups. Future studies should interrogate inter-ethnic dynamics on a broader scale, and explore ethnic bullying and its impact on inter-ethnic relations.